British art and the First World War, 1914-1924 - Fox, James 1982- (Studies in the social and cultural history of modern warfare, 2015)
The First World War is usually believed to have had a catastrophic effect on British art, killing artists and movements, and creating a mood of belligerent philistinism around the nation. In this book, however, James Fox paints a very different picture of artistic life in wartime Britain. Drawing on a wide range of sources, he examines the cultural activities of largely forgotten individuals and institutions, as well as the press and the government, in order to shed new light on art's unusual role in a nation at war. He argues that the conflict's artistic consequences, though initially disruptive, were ultimately and enduringly productive. He reveals how the war effort helped forge a much closer relationship between the British public and their art - a relationship that informed the country's cultural agenda well into the 1920s